Adherence to World Cancer Research Fund/American Institute for Cancer Research Recommendations and Pancreatic Cancer Risk - Lucas, Aimee L. (Cancer Epidemiol, 2015)
BACKGROUND: Pancreatic cancer is a leading cause of cancer death. A role of dietary factors in pancreatic carcinogenesis has been suggested. The World Cancer Research Fund (WCRF) and the American Institute for Cancer Research (AICR) published 8 recommendations for cancer prevention. We evaluated the effect of adherence to the WCRF/AICR recommendations on pancreatic cancer risk. METHODS: We operationalized 7 of the 8 WCRF/AICR recommendations to generate a WCRF/AICR score. We examined the association of WCRF/AICR score with pancreatic cancer in data from an Italian case-control study of 326 incident cases and 652 controls. RESULTS: Adherence to WCRF/AICR recommendations was associated with a significantly decreased risk of pancreatic cancer. Using a WCRF/AICR score <3.5 as a reference, the adjusted odds ratio (OR) for a score 3.5 to <4 was 0.80 (95% CI 0.49, 1.28), for a score 4 to <5 0.54 (95% CI 0.35, 0.82), and for score 5 or more 0.41 (95% CI 0.24, 0.68; p-value for trend 0.0002). The OR for a continuous increment of one unit of the WCRF/AICR score was 0.72 (95% CI 0.60, 0.87). CONCLUSION: Adherence to the WCRF/AICR recommendations may reduce pancreatic cancer risk.